Biomonitoring the genetic effects of environmental tobacco smoke exposure in restaurant workers - Vital, Nádia (2014)
Environmental tobacco smoke (ETS) is recognized as one of the most common indoor pollutants worldwide. Portuguese legislation prohibits smoking in most indoor public spaces. However, in some restaurants/bars smoking is still allowed, representing a potential risk factor for the workers health, particularly for chronic respiratory diseases and cancer onset.The aim of this study was to characterize early signs of ETS-associated adverse systemic effects in workers from restaurants with smoking permission in comparison with workers from smoke-free spaces, considering the modulating effects of genetic susceptibility.The ETS-exposed workers did not display differences in the frequencies of SCEs, cells with high frequency of SCEs (HFCs), MN or DNA strand breaks, as assessed by the comet assay, when compared to non-ETS workers. Smoking workers presented a significantly increased level of HFCs as compared to non-smokers. Interestingly, the ex vivo challenge of leukocytes with EMS resulted in a lower level of DNA breaks in ETS-exposed as compared to non-exposed workers (P<0,0001), suggesting an increased DNA repair capacity associated to ETS-exposure. Regarding the genetic polymorphisms studied, GSTM1 null genotype carriers presented increased frequencies of SCEs and HFCs associated with ETS exposure, suggesting an increased susceptibility to this environmental stressor. On the contrary, XRCC1-399 wild type carriers presented a lower level of MN than the variant allele carriers, in response to ETS exposure. Finally, among the ETS-exposed subjects, those carrying the hOGG1 variant alleles presented a lower level of ex vivo EMS-induced DNA damage comparatively to the wild type subjects, suggesting a higher DNA repair capacity.The study of ETS exposure in an occupational setting in Lisbon restaurants revealed that the exposed workers did not display systemic genetic effects detectable by the biomarkers analysed. However, the results of the ex vivo challenge comet assay, suggests that ETS may have a more subtle modulating effect on the DNA repair response of blood cells to a genotoxic insult. In addition, the association between some genetic polymorphisms and increased genotoxic effects in subsets of individuals, highlights the possibility of increased health risks in susceptible individuals exposed to ETS, that should be further investigated.